2004
DOI: 10.1097/01.prs.0000130972.59268.aa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Povidone Iodine on Silicone Gel Breast Implants In Vitro: Implications for Clinical Practice

Abstract: Irrigation of breast implants and breast implant pockets with various solutions, including povidone iodine, has been a common practice among plastic surgeons for many years. Recent reports of potential weakening of silicone tubing have led the Food and Drug Administration to pronounce any contact of povidone iodine with breast implants a contraindication. An in vitro experimental study was undertaken to assess the effect of povidone iodine on the physical properties of silicone breast implant shells. Identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…We do not disagree with many who find it illogical that the Food and Drug Administration has not reconsidered its strange decision to restrict povidone-iodine usage when there have now been multiple studies that have not found any detrimental implant effect of extraluminal povidone-iodine. 15,16,27,28 Despite the bureaucracy of this process, keep in mind that the off-label use of povidone-iodine-containing breast irrigation is still permissible at the discretion of the operating surgeon. In this situation, the surgeon can disclose the intention to use povidone-iodine to the patient with appropriate background information, and we have found patients to be not only accepting but grateful that their physician is acting in their best interest.…”
Section: Discussionmentioning
confidence: 99%
“…We do not disagree with many who find it illogical that the Food and Drug Administration has not reconsidered its strange decision to restrict povidone-iodine usage when there have now been multiple studies that have not found any detrimental implant effect of extraluminal povidone-iodine. 15,16,27,28 Despite the bureaucracy of this process, keep in mind that the off-label use of povidone-iodine-containing breast irrigation is still permissible at the discretion of the operating surgeon. In this situation, the surgeon can disclose the intention to use povidone-iodine to the patient with appropriate background information, and we have found patients to be not only accepting but grateful that their physician is acting in their best interest.…”
Section: Discussionmentioning
confidence: 99%
“…Although early studies postulated a theoretical risk of deflation with betadine, 8,9 more recent research (as well as our own experience) indicates that this is not the case. 10 With studies confirming the protective effect against capsular contracture in vitro, 11 this factor may be a significant contributor to the low capsular contracture rate seen in this study.…”
Section: Discussionmentioning
confidence: 51%
“…The minor disruptions induced by a smooth brush on the prosthesis were insignificant compared to the tests performed at the factory (Mentor Ò Corporation Santa Barbara, Calif.). Moreover, the decision to use Betadine was also affirmed by the experimental study of Zambacos and Nguyen [26], who studied the effects of different concentrations of povidone-iodine (0.01-10%) on silicone shells and found no structural modification [26]. In other words, a brief contact of the implant with Betadine, during the decontamination procedure, and followed by copious saline solution irrigation, has no effect on the long-term integrity of the shell of the implant.…”
Section: Discussionmentioning
confidence: 92%